(untitled) (Riwayat: Educational Journal of History and Humanities, 2026)
This study aims to determine the effect of the accounting information system and the quality of the internal control system on the quality of financial statements at PT Alfath Corporation Indonesia. This study uses a quantitative approach with data obtained through the spread of questionnaires to 71 respondents who are employees of the company. Data analysis was carried out using SPSS software with testing in the form of validity test, reliability test, normality test, heterocedasticity test, multiple linear regression analysis, partial test, and determination coefficient test. The results showed that all research instruments met valid and reliable criteria and data filled the classical assumptions. Based on the results of multiple linear regression analysis and t test, the accounting information system has a significant effect on the quality of financial statements. This shows that the application of a good information system is able to support the presentation of relevant, accurate and relevant financial statements. In addition, the quality of the internal control system also has a significant effect on the quality of financial statements, which indicates that an effective internal control mechanism can minimize errors and improve the reliability of financial information. Thus, it can be concluded that the accounting information system and the quality of the internal control system influence the quality of financial statements at PT Alfath Corporation Indonesia.